Inhabiting a Chaos-World: Refugee Transnational Identities in Mohsin Hamid’s Exit West (2017) - Tosi, Valerie (Il Tolomeo)
This article explores Mohsin Hamid’s novel Exit West (2017) combining principles pertaining to social geography, affect theory, and (post)migration studies with postcolonial theory. It aims to highlight how Hamid’s use of magical realism triggers political, philosophical, and socio-emotional reflections by condensing in the story arc the intercultural and intersubjective processes that characterise the migratory experience and the postmigrant condition. Firstly, it investigates how Exit West incorporates magical realism to represent the psychoemotional dynamics of migration and to problematize the concept of cosmopolitanism; secondly, it discusses how the novel promotes a re-thinking of migration identities and experiences in terms of affective transnationality; thirdly, it points out how the refugee communities represented in the novel are manifestations of a chaos-world in which identity formation is shaped by sociocultural encounters, multilingualism, media use, and processes of affiliation.